Breast cancer quality of life evaluation in Mexican Women at La Raza Hospital, Mexico City: A preliminary approach - Jacobo Alejandro Gómez-Rico; Marina Altagracia-Martínez; Jaime Kravzov-Jinich; Rosario Cárdenas-Elizalde; Juan Carlos Hinojosa-Cruz; Consuelo Rubio-Poo (Dove Medical Press, 2008)
Jacobo Alejandro Gómez-Rico1, Marina Altagracia-Martínez1, Jaime Kravzov-Jinich1, Rosario Cárdenas-Elizalde1, Juan Carlos Hinojosa-Cruz2, Consuelo Rubio-Poo31Departments of Biological Systems and Healthcare, Biological and Health Sciences Division (DCBS), Universidad Autónoma Metropolitana–Xochimilco (UAM-X), Xochimilco, Mexico; 2La Raza Hospital of the Mexican Social Security Institute (IMSS), Mexico City, Mexico; 3Universidad Nacional Autónoma de México (UNAM), Faculty of Professional Studies, Zaragoza (FES-Zaragoza), MexicoAbstract: Breast cancer (BC) is the second leading cause of death among Mexican women over 40 years of age. This study aimed to identify and examine the effects of cancer stage and surgical treatment on the quality of life (QOL) of Mexican women with early stage breast cancer (ESBC) treated with either modified radical mastectomy (MRM) or breast conservative surgery (BCS), plus adjuvant chemotherapy. The QLQ-C30 and QLQ BR-23 questionnaires were used to assess QOL. Sociodemographic characteristics and clinical factors of 102 women with early BC were also evaluated; analysis of variance (ANOVA) was performed and a statistical significance of p < 0.05 was assumed. Most women were of reproductive age. Meaningful differences in QOL as a result of surgical treatment, in women receiving BCS compared with those receiving MRM, were limited to body image. We conclude that MRM and BCS are essentially equivalent choices in terms of QOL, with the exception of the impact on body image. In general, women who received BCS had a better perceived QOL.Keywords: quality of life, breast cancer, Mexican women